2006
DOI: 10.1037/0022-0663.98.2.282
|View full text |Cite
|
Sign up to set email alerts
|

A portrait of benchmark school: How a school produces high achievement in students who previously failed.

Abstract: This is a case study of Benchmark School, which educates 6-to 15-year-olds with a history of school failure. Grounded theory methodology was employed to generate a theory about how the school promotes achievement. Many elements potentially promoting academic achievement were identified, including ones informed by psychological theory and research (e.g., evidence-based literacy instructional practices, strategies instruction, conceptually focused content instruction, many mechanisms to motivate students) but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 71 publications
2
52
0
Order By: Relevance
“…Highly effective writing teachers recognize that the physical environment of the classroom can facilitate students' writing motivation and development (Pressley et al, 2004(Pressley et al, , 2006. Their class libraries are expansive in both breadth and depth.…”
Section: Physical Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly effective writing teachers recognize that the physical environment of the classroom can facilitate students' writing motivation and development (Pressley et al, 2004(Pressley et al, , 2006. Their class libraries are expansive in both breadth and depth.…”
Section: Physical Environmentmentioning
confidence: 99%
“…Finally, highly effective writing teachers furnish and arrange their classrooms to be conducive to learning (Pressley et al, 2006;. For instance, they ensure that all students have a variety of options for working comfortably, such as at a desk, in a beanbag chair, on a couch, and at a table.…”
Section: Physical Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that 40% -60% students have no active participation in school as they progress from elementary onto middle and then to high school [1] and perceive lack of opportunities [2,3] . Low engagement in learning among students leads to dissatisfaction, negative experience, and rise in drop outs [4][5][6] .…”
mentioning
confidence: 99%
“…This approach is aligned with the well-known importance of involving parents to support their child's development across diverse areas, such as school belonging, engagement with learning, and academic achievement (Adi, Killoran, Janmohamend, & Stewart-Brown, 2007;Comer & Haynes, 1991;Epstein, 1987;Grolnick, Benjet, Kurowski, & Apostoleris, 1997;Pressley, Gaskins, Solic, & Collins, 2006;Shucksmith, Summerbell, Jones, & Whittaker, 2007). As noted by Weare (2010, p. 5), good practice in mental health promotion in schools requires "teamwork between the appropriate agencies including parents and students".…”
Section: Examples Of School-based Mental Health Promotion Initiativesmentioning
confidence: 99%